Adalimumab drug and antidrug antibody levels do not predict flare risk after stopping adalimumab in RA patients with low disease activity. (31st October 2018) - Lamers-Karnebeek, Femke B G; Jacobs, Johannes W G; Radstake, Timothy R D J; van Riel, Piet L C M; Jansen, Tim L
Abstract: Objective: To establish whether serum adalimumab (ADA) trough level (ADA-TL) and antidrug antibody (ADA-ab) level predict flare after stopping ADA in established RA patients with long-standing low disease activity. Methods: From the clinical trial Potential Optimalisation and Effectiveness of TNF-blockers, 210 RA patients stopping ADA, who had been using ADA (40 mg/2 weeks) for >1 year with conventional synthetic DMARDs and who had low disease activity (DAS28 < 3.2, or the rheumatologist's assessment of low disease activity with CRP < 10 mg/l) for at least 6 months prior to stopping, were followed for 1 year. The ADA-TL was measured (by ELISA) 12–17 days after the last ADA injection; if it was low, ADA-abs were measured (by an antigen-binding test). Association between time-to-flare and ADA-TL was evaluated by area under the receiver operating characteristic curve and Cox regression. Results: A total of 106 (51%) patients flared within 1 year after stopping ADA. The area under the receiver operating characteristic curve for flare and ADA-TL was 0.50 (95% CI 0.42–0.58), P = 0.92. The hazard ratio for flare for ADA-TL ⩾ 5 μg/ml (adequate level) vs <5 μg/ml was 0.93 (95% CI: 0.63–1.36) (not significant). Of the 4 patients with high ADA-ab levels, 2 patients (50%) experienced a flare. Conclusion: Flare risk within the year following stopping ADA is not predicted by the ADA-TL or ADA-abs assessed at the moment of stopping. Trial registration: Netherlands Trial Register, http://www.trialregister.nl, NTR3112.